SERS Probing of Proteins in Gold Nanoparticle Agglomerates - Szekeres, Gergo Peter; Kneipp, Janina (Frontiers in Chemistry, 2019)
The collection of surface-enhanced Raman scattering (SERS) spectra of proteins and other biomolecules in complex biological samples such as animal cells has been achieved with gold nanoparticles that are introduced to the sample. As a model for such a situation, SERS spectra were measured in protein solutions using gold nanoparticles in the absence of aggregating agents, allowing for the free formation of a protein corona. The SERS spectra indicate a varied interaction of the protein molecule with the gold nanoparticles, depending on protein concentration. The concentration-dependent optical properties of the formed agglomerates result in strong variation in SERS enhancement. At protein concentrations that correspond to those inside cells, SERS signals are found to be very low. The results suggest that in living cells the successful collection of SERS spectra must be due to the positioning of the aggregates rather than the crowded biomolecular environment inside the cells. Experiments with DNA suggest the suitability of the applied sample preparation approach for an improved understanding of SERS nanoprobes and nanoparticle-biomolecule interactions in general.